2013
DOI: 10.1186/1752-1947-7-214
|View full text |Cite
|
Sign up to set email alerts
|

Primary cervical spine carcinoid tumor in a woman with arm paresthesias and weakness: a case report

Abstract: IntroductionCarcinoid tumors are neuroendocrine neoplasms derived from the enterochromaffin cells. Central nervous system involvement is rare and has been reported either as metastases to the brain and spine or primary tumors involving the sacrococcygeal spine. We report the first case of a primary carcinoid tumor of the cervical spine.Case presentationA 50-year-old African-American woman presented with a 4-month history of numbness, paresthesias, and mild left-hand weakness. Magnetic resonance imaging of her … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Carcinoid tumors were of bronchial (n = 9) and nonpulmonary origin (n = 17)-of which CNS (n = 2) and thymus (n = 3)-, and 4 patients had carcinoid tumors of unknown primary, whereas in 7 patients, the origin was not specified. [16][17][18][19][20][21][22][23][24][26][27][28][29][30][31][32]34,35,37,38,43 Only 6 pNET cases, including ours, of malignant spinal cord compression have been reported in the literature, 25,33,36,40,41 with two of them due to "functional" pNETs (ie, glucagonoma, gastrinoma). As far as we know, our case is the first ever reported of a pNETwith an "intradural" metastasis to the spinal cord, and we only found the following 4 other cases of spinal intradural NET metastases: 2 thymic carcinoids, 28,35 1 lung atypical carcinoid, 18 and a probable primary atypical carcinoid of the CNS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Carcinoid tumors were of bronchial (n = 9) and nonpulmonary origin (n = 17)-of which CNS (n = 2) and thymus (n = 3)-, and 4 patients had carcinoid tumors of unknown primary, whereas in 7 patients, the origin was not specified. [16][17][18][19][20][21][22][23][24][26][27][28][29][30][31][32]34,35,37,38,43 Only 6 pNET cases, including ours, of malignant spinal cord compression have been reported in the literature, 25,33,36,40,41 with two of them due to "functional" pNETs (ie, glucagonoma, gastrinoma). As far as we know, our case is the first ever reported of a pNETwith an "intradural" metastasis to the spinal cord, and we only found the following 4 other cases of spinal intradural NET metastases: 2 thymic carcinoids, 28,35 1 lung atypical carcinoid, 18 and a probable primary atypical carcinoid of the CNS.…”
Section: Discussionmentioning
confidence: 98%
“…42 Most of the cases (n = 35) are in fact extradural spinal cord compressions due to vertebral metastases with an epidural soft tissue component. 16,19,[21][22][23][24][25][26]29,[32][33][34][35][36][37][38][39]41,43 Reported cases include carcinoid tumors (n = 36), pNET (n = 6), and NETs of unknown primary (n = 3). Carcinoid tumors were of bronchial (n = 9) and nonpulmonary origin (n = 17)-of which CNS (n = 2) and thymus (n = 3)-, and 4 patients had carcinoid tumors of unknown primary, whereas in 7 patients, the origin was not specified.…”
Section: Discussionmentioning
confidence: 98%
“…The patient underwent a C7–T1 en bloc resection of a carcinoid tumor and had no evidence of recurrence at 6 years' follow-up. 24 En bloc spondylectomy was performed on a 56-year-old woman with tumor-induced osteomalacia secondary to a fibroblast growth factor 23–secreting phosphaturic mesenchymal tumor in the T8 vertebral body. The en bloc resection successfully treated this metabolically active tumor and resolved her tumor-induced osteomalacia, with fibroblast growth factor 23 levels returning to normal 14 months after surgery ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the limited reports available, en bloc resection appears to be a potential surgical option for functionally active spinal metastasis able to control the tumor-induced sequelae and offer potential long-term local tumor control. 15 18 22 24 Although an analysis of the local recurrence and/or long-term survival cannot be estimated based on the rarity of these tumor subtypes, one could hypothesize that in the absence of effective adjuvant treatment, intralesional resections have the potential to lead to increased local recurrence when compared with en bloc resection for any functional secretory spinal metastasis. Intralesional resections could potentially spill tumor into the resection cavity, leaving behind secretory tumor.…”
Section: Discussionmentioning
confidence: 99%
“…There is one case report of carcinoid tumor occurring in cervical spine [9]. Covelli et al [10] reported a case of a patient who had both a malignant carcinoid tumor in small intestine as well as a malignant retroperitoneal paraganglioma occurring synchronously.…”
Section: Discussionmentioning
confidence: 98%